PROBLEMATIKA PENEGAKAN HUKUMAN DISIPLIN KEPEGAWAIAN - Tedi Sudrajat, Tedi Sudrajat (Faculty of Law, Universitas Jenderal Soedirman, 2008)
This Article is mention to describe the existence of administrative law that inherent with the activity of public servants and it makes many consequences in the term of law enforcement. Based on the analysis of the administrative system, there are many problems in the structure, substance and culture of its legal system. The problems in those three aspects can be seen in the substance of President Regulation No.30 year 1980 that gave the opportunity for the infraction. The substance also influences the structure and the culture in the activity of the public servant. Kata kunci : Administrasi Kepegawaian, Pegawai Negeri Sipil dan Pelanggaran Disiplin